Economic polarization in the European Union: Development models in the race for the best location - Jonas Dominy; Claudius Gräbner-Radkowitsch; Philipp Heimberger; Jakob Kapeller (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2025)
This paper analyzes developmental trajectories in the EU. In doing so, it diagnoses economic polarization on two different levels: for one, we observe a divergence of average incomes across EU countries as a persistent empirical feature associated with European integration. For another, European economic integration in general and the introduction of the Euro in particular are associated with the emergence of heterogeneous developmental trajectories, which build on, and intensify differences in technological capabilities, institutional and legal setups, as well as labor market characteristics. When clustering countries with reference to similarities in terms of macroeconomic and institutional characteristics across countries, we find evidence for the existence of four distinct development models: core, periphery, and workbench economies, as well as financial hubs. Each of these groups is defined by distinct technological, institutional, and macroeconomic characteristics. Our findings point to suitable ways for extending and refining existing typological approaches, such as the Varieties of Capitalism or the growth model approach, thereby allowing us to better account for the heterogeneity of developmental pathways emerging in the course of an intensifying European race for the best location.
Keywords: B5; F6; F45; 330; Economic polarization; European integration; Development models; growth models; European Union